Síntese de dados sobre as propriedades de biocarvões brasileiros e influência sobre a disponibilidade de fósforo em solos - Santana, Maria Júlia Bonfim (2022)
Biochar is a material that has been intensively researched around the world. In Brazil, the current motivation for studying biochar is to recycle commodity byproducts and develop high-performance soil conditioners. However, advances in biochar research have not been systematically evaluated in Brazil, and possible gaps may guide future research. Thus, in this work, the influence of temperature and material on the main properties of biochars was evaluated based on data collected in a Brazilian study, and the effect of biochar on phosphorus availability in soils with contrasting mineralogy was determined. The work was divided into two stages: in the first stage, a systematic review was carried out based on the selection and analysis of information obtained from 57 publications. In the second stage, sugarcane and orange bagasse biochars were produced at 300 ºC and 500 ºC, with and without washing to remove the ash. Biochars were mixed in soils with varied mineralogical compositions in which the interaction with phosphate was evaluated from the remaining phosphorus methodology. The first stage results indicated that most research carried out the characterization and considered biochar a soil conditioner. The pyrolysis temperature and the raw material determine most biochars' properties. Future research should prioritize long-term evaluations of biochar under field conditions and the development of technological applications. The second stage results indicated that sugarcane biochar obtained at a temperature of 300 ºC when added to the soil was more efficient in reducing retained phosphate, especially in soils with higher goethite contents. Thus, biochars have the potential as a soil improver under the efficiency of the use of phosphate by plants.